Clinical features and mutational analysis of X-linked agammaglobulinemia patients in Malaysia - Chear, Chai Teng; Ismail, Intan Hakimah; Chan, Kwai Cheng; Noh, Lokman Mohd; Kassim, Asiah; Latiff, Amir Hamzah Abdul; Gill, Sandeep Singh; Ramly, Nazatul Haslina; Tan, Kah Kee; Sundaraj, Charlotte; Choo, Chong Ming; Mohamed, Sharifah Adlena Syed; et al. (Frontiers in Immunology, 2023)
Background: Bruton's tyrosine kinase (BTK) is a cytoplasmic protein involved in the B cell development. X-linked agammaglobulinemia (XLA) is caused by mutation in the BTK gene, which results in very low or absent B cells. Affected males have markedly reduced immunoglobulin levels, which render them susceptible to recurrent and severe bacterial infections.Methods: Patients suspected with X-linked agammaglobulinemia were enrolled during the period of 2010-2018. Clinical summary, and immunological profiles of these patients were recorded. Peripheral blood samples were collected for monocyte BTK protein expression detection and BTK genetic analysis. The medical records between January 2020 and June 2023 were reviewed to investigate COVID-19 in XLA.Results: Twenty-two patients (from 16 unrelated families) were molecularly diagnosed as XLA. Genetic testing revealed fifteen distinct mutations, including four splicing mutations, four missense mutations, three nonsense mutations, three short deletions, and one large indel mutation. These mutations scattered throughout the BTK gene and mostly affected the kinase domain. All mutations including five novel mutations were predicted to be pathogenic or deleterious by in silico prediction tools. Genetic testing confirmed that eleven mothers and seven sisters were carriers for the disease, while three mutations were de novo. Flow cytometric analysis showed that thirteen patients had minimal BTK expression (0-15%) while eight patients had reduced BTK expression (16-64%). One patient was not tested for monocyte BTK expression due to insufficient sample. Otitis media (n=12)Pneumonia (n=13) was the most common manifestation, while Pseudomonas aeruginosa was the most frequently isolated pathogen from the patients (n=4). Mild or asymptomatic COVID-19 was reported in four patients.This report provides the first overview of demographic, clinical, immunological and genetic data of XLA in Malaysia. The combination of flow cytometric assessment and BTK genetic analysis provides a definitive diagnosis for XLA patients, especially with atypical clinical presentation. In addition, it may also allow carrier detection and assist in genetic counselling and prenatal diagnosis.